Burden of Emergency Pediatric Surgical Procedures on Surgical Capacity in Uganda: A New Metric for Health System Performance - Grabski, David F.; Kakembo, Nasser; Situma, Martin; Cheung, Maija; Shikanda, Anne; Okello, Innocent; Kisa, Phyllis; Muzira, Arlene; Sekabira, John; Ozgediz, Doruk (Surgery, 2020)
The significant burden of emergency operations in low- and middle-income countries can overwhelm surgical capacity leading to a backlog of elective surgical cases. The purpose of this investigation was to determine the burden of emergency procedures on pediatric surgical capacity in Uganda and to determine health metrics that capture surgical backlog and effective coverage of children’s surgical disease in low- and middle-income countries.We reviewed 2 independent and prospectively collected databases on pediatric surgical admissions at Mulago National Referral Hospital and Mbarara Regional Referral Hospital in Uganda. Pediatric surgical patients admitted at either hospital between October 2015 to June 2017 were included. Our primary outcome was the distribution of surgical acuity and associated mortality.A combined total of 1,930 patients were treated at the two hospitals, and 1,110 surgical procedures were performed. There were 571 emergency cases (51.6%), 108 urgent cases (9.7%), and 429 elective cases (38.6%). Overall mortality correlated with surgical acuity. Emergency intestinal diversions for colorectal congenital malformations (anorectal malformations and Hirschsprung’s disease) to elective definitive repair was 3:1. Additionally, 30% of inguinal hernias were incarcerated or strangulated at time of repair.Emergency and urgent operations utilize the majority of operative resources for pediatric surgery groups in low- and middle-income countries, leading to a backlog of complex congenital procedures. We propose the ratio of emergency diversion to elective repair of colorectal congenital malformations and the ratio of emergency to elective repair of inguinal hernias as effective health metrics to track this backlog. Surgical capacity for pediatric conditions should be increased in Uganda to prevent a backlog of elective cases.